KARAKTERISTIK KAUM MUDA PADA PASAR TENAGA KERJA DAN DETERMINAN NEET DI INDONESIA - Mirta Dwi Wulandari; Elfrida Zoraya (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2021)
In Indonesia, young people are, according to BPS-Statistics Indonesia, almost one-fifth of the total population. Despite increasing general emphasis on youth employment, there is still an alarming issue from unemployment among youth since it was very high and likely to increase further. Recent Indonesia labour force survey shows that youth unemployment is 19.7% in 2018, while the rate of NEET young people reached 22.1%. For this study will be analyzed several indicators like youth vulnerability in labor market, unemployment rate, and NEET. This study identify how youth unemployment and the NEET proportion in Indonesia. This study uses logistic binary analysis methods using SAKERNAS 2018 data to identify the determinants of NEET. The results obtained are social and demographic characteristics affecting young people to become NEET.